THE RELATIONSHIP OF SUPERVISIORY COMPETENCY AND SCHOOL LEADERSHIP WITH TEACHER PERFORMANCE IN ZONA I ELEMENTARY SCHOOL, PANDEGLANG DISTRICT - Wawan Wantoro; Is Eka Herawati (JPSD (Jurnal Pendidikan Sekolah Dasar), 2020)
AbstractThe Research is motivated by reality in the field, where teachers have a strategic role in improving the quality of education in schools. The purpose of this research is to examine the relationship between supervisory competence and school leadership with teacher performance. This research was conducted on elementary schools in Zone 1 of Pandeglang Regency. The method used was a survey technique with a Likert scale, using a questionnaire with a sample of 168 respondents. The analysis of research data using descriptive analysis, simple regression and multiple regressions with the SPSS software version 20 for windows. From the estimated standard for supervisory competency variables (X1), school leadership (X2) and teacher performance (Y), with the equation Y = 32.973 + 0.116X1 + 0.155X2. The analysis results are in the level of the close relationship between supervisory competence and school's leadership along with the teachers’ performance are 0,467 that included in the medium category. Meanwhile the contribution magnitude of the supervisory competence and school leadership variables along with the teachers' performance was 21.8% and the remaining 78.2% was contributed by other factors outside the research model.Keywords: Principal Supervision Competencies, School Leadership and Teachers Performance.